Metodología cuantitativa y cualitativa en la investigación sobre la formación inicial del profesorado de educación musical para primaria. Aplicación a la formación instrumental - Oriol, Nicolás (Revista Electrónica Complutense de Investigación en Educación Musical - RECIEM, 2004)
The investigation herein, within the Social and Musical Sciences, is descriptive and is directed fundamentally at understanding the instrumental skills of the Teacher in Musical Education students at the moment of starting their studies, the skills they acquire during their studies, and the skills developed when graduating, as well as the implications for teaching in primary schools. The universe investigated is circumscribed to students and staff of the Faculty of Education of the Universidad Complutense de Madrid during the academic year 2000-2001. The research model has been multimethodical, through the use of quantitative and qualitative methodology.